2022
DOI: 10.1002/mp.15706
|View full text |Cite
|
Sign up to set email alerts
|

A 2D strip ionization chamber array with high spatiotemporal resolution for proton pencil beam scanning FLASH radiotherapy

Abstract: Purpose Experimental measurements of two‐dimensional (2D) dose rate distributions in proton pencil beam scanning (PBS) FLASH radiation therapy (RT) are currently lacking. In this study, we characterize a newly designed 2D strip‐segmented ionization chamber array (SICA) with high spatial and temporal resolution and demonstrate its applications in a modern proton PBS delivery system at both conventional and ultrahigh dose rates. Methods A dedicated research beamline of the Varian ProBeam system was employed to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 53 publications
(188 reference statements)
2
31
0
Order By: Relevance
“…This is because the Lynx detector's count range, 0 to 1000, limits its ability to measure low-dose tails with reasonable accuracy; ± 1.5 cm is coincident with counts falling below 10 −3 (normalized value). This is where the profile deviates significantly from a single Gaussian significantly, as shown previously by several investigators [ 29 , 31 , 32 ]. R-square and root-mean-square-error values are obtained by considering the points above the 10 −3 threshold.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This is because the Lynx detector's count range, 0 to 1000, limits its ability to measure low-dose tails with reasonable accuracy; ± 1.5 cm is coincident with counts falling below 10 −3 (normalized value). This is where the profile deviates significantly from a single Gaussian significantly, as shown previously by several investigators [ 29 , 31 , 32 ]. R-square and root-mean-square-error values are obtained by considering the points above the 10 −3 threshold.…”
Section: Discussionsupporting
confidence: 70%
“…Although they have not reached FLASH DRs, their study shows that beam spot size and energy are not DR-dependent. However, under FLASH conditions, beam optics (due to the space charge effect of densely bunched protons) and beamline configuration (like removal of some component or change of steering parameters) can change, prompting spot profile comparison of conventional and FLASH beams [ 28 , 29 ]. This type of comparison was not performed in this work and is a limitation of this study.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the measured dose profile found by a 2D strip segmented ionization chamber array was used for PBS dose rate calculations. 28 A functional form of the lateral dose profile that includes the tails of the dose profile was used in that study and the PBS dose rate pattern yielded comparable results with our PBS dose rate map using the measured dose profile (Figure 8b).…”
Section: Discussionmentioning
confidence: 53%
“…The PBS dose rate map calculated previously for the same field and beam parameters 6 yielded similar results as the case of a Gaussian profile in this study (max DR PBS95% = 531 Gy/s, Figure 8c), but the maximum PBS dose rate (418 Gy/s) was lower due to a larger Gaussian width (σ x = 3.9 mm and σ y = 4.1 mm) and lower field dose rate (77 Gy/s) used in the simulation. In another study, the measured dose profile found by a 2D strip segmented ionization chamber array was used for PBS dose rate calculations 28 . A functional form of the lateral dose profile that includes the tails of the dose profile was used in that study and the PBS dose rate pattern yielded comparable results with our PBS dose rate map using the measured dose profile (Figure 8b).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation